2023
DOI: 10.1088/1752-7163/acaf98
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an individual with background levels of exhaled isoprene: a case study

Abstract: Isoprene is one of the most abundant and most frequently evaluated volatile organic compounds in exhaled breath. Recently, several individuals with background levels of exhaled isoprene have been identified. Here, case study data are provided for an individual, identified from a previous study, with this low prevalence phenotype. It is hypothesized that the individual will illustrate low levels of exhaled isoprene at rest and during exercise. At rest, the subject (7.1ppb) shows background (μ=14.2±7.0ppb) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…An exception to this is participant 2’s mass spectra for mint and tobacco-flavored trials (Figure S7a,b). These trials had low signal and the dominant peaks were acetone ( m / z 59) and isoprene ( m / z 69), normal baseline substituents of human breath. Participants 2 and 3 smoked the same vape device and e-liquids, but in comparison to participant 3, participant 2 generated lower intensity mass spectra (Figure S7) for mint and tobacco trials, and mass spectral peaks did not resemble other participant trials. This result reflects the variability in emissions depending on how a participant interacts with their vape device and how personal habits influence VOC mass concentrations…”
Section: Resultsmentioning
confidence: 99%
“…An exception to this is participant 2’s mass spectra for mint and tobacco-flavored trials (Figure S7a,b). These trials had low signal and the dominant peaks were acetone ( m / z 59) and isoprene ( m / z 69), normal baseline substituents of human breath. Participants 2 and 3 smoked the same vape device and e-liquids, but in comparison to participant 3, participant 2 generated lower intensity mass spectra (Figure S7) for mint and tobacco trials, and mass spectral peaks did not resemble other participant trials. This result reflects the variability in emissions depending on how a participant interacts with their vape device and how personal habits influence VOC mass concentrations…”
Section: Resultsmentioning
confidence: 99%
“…The parallel increase of breath isoprene with increasing muscle mass with age provides additional support for the hypothesis that isoprene production is related to muscle tissue. Although isoprene is a commonly found endogenous volatile in exhaled breath in high levels, as mentioned previously a few studies have found subjects (approximately 1 in a 1000) whose isoprene levels are deficient or completely absent (below the detection limit) [3,5,6,26,27,34,47,48]. The cause of this lack of production is uncertain.…”
Section: Steady State Isoprene Concentrations In Exhaled Breathmentioning
confidence: 97%
“…Nevertheless, a single rare case was insufficient for detailed down-stream multi-omic analysis to determine the exact source. In a recent case study on one isoprene deficient American adult male and his blood-relatives by Harshman et al 41 and in another study on an isoprene deficient Italian adult female and her blood-relatives by Biagini et al 42 also demonstrated no relation of exhaled isoprene profiles to plasma cholesterol levels. They neither find any isoprene absent rare adult nor investigated the human cholesterol metabolism related gene expressions.…”
Section: Introductionmentioning
confidence: 93%